2020
DOI: 10.1007/s10592-020-01296-0
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation technologies applied to age-old challenges in Madagascar

Abstract: Madagascar is a biodiversity hotspot that is facing rapid rates of deforestation, habitat destruction, and poverty. Urgent action is required to document the status of biodiversity to facilitate efficacious conservation plans. With the recent advent of portable and affordable genetic technologies, it is now possible to take genomic approaches out of the lab and into the field. Mobile genetics labs can produce scientifically reproducible data under field conditions, dramatically minimizing the time between samp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…This work is informed by foundational efforts that identified legislation for which genetic diversity is relevant (Laikre et al 2010 , Santamaría and Méndez 2012 ). Genetic diversity assessment capacity is also emerging in lower-income, high-biodiversity regions (Torres-Florez et al 2018 ), including through international collaborations (Blanco et al 2020 ). Efforts are also being made to identify barriers preventing practitioners from using genetic data (Taylor et al 2017 ), synthesize the evidence base to guide decision-making (Cook and Sgrò 2017 ), determine how frequently genetic research findings are used by nature management agencies (Bowman et al 2016 ), improve dissemination and accessibility of genetic findings (Hoban et al 2013 ), and increase the relevance of research to practice and policy (Taft et al 2020 ).…”
Section: Second Set Of Conditions: Monitoring Toolsmentioning
confidence: 99%
“…This work is informed by foundational efforts that identified legislation for which genetic diversity is relevant (Laikre et al 2010 , Santamaría and Méndez 2012 ). Genetic diversity assessment capacity is also emerging in lower-income, high-biodiversity regions (Torres-Florez et al 2018 ), including through international collaborations (Blanco et al 2020 ). Efforts are also being made to identify barriers preventing practitioners from using genetic data (Taylor et al 2017 ), synthesize the evidence base to guide decision-making (Cook and Sgrò 2017 ), determine how frequently genetic research findings are used by nature management agencies (Bowman et al 2016 ), improve dissemination and accessibility of genetic findings (Hoban et al 2013 ), and increase the relevance of research to practice and policy (Taft et al 2020 ).…”
Section: Second Set Of Conditions: Monitoring Toolsmentioning
confidence: 99%
“…Lastly, innovations in portable labs have also enhanced our ability to remotely detect primates. Several studies have demonstrated the possibility of using portable sequencers for species identification in the field through DNA barcoding, which is limited to one gene region per sample (Blanco et al 2020;Menegon et al 2017;Pomerantz et al 2018). Further, metabarcoding offers the potential to sequence mixed DNA barcode amplicons from bulk community or pooled samples (Krehenwinkel et al, 2019b).…”
Section: Avenues For Investigationmentioning
confidence: 99%
“…The process of extracting and sequencing DNA was rapid (~2 hr), mobile, and cost-effective (<US$1.00 per sample). Additionally, DNA amplification using PCR and subsequent detection by electrophoresis have been performed on site for microsatellite genotyping of two primate species (Propithecus verreauxi and P. coquereli) in Madagascar (Guevara et al 2018) (Guevara et al 2018), and a fully portable field lab including the MinION facilitated the molecular species assignment of a Malagasy lemur species within a week, from animal capture to tissue collection, to phylogenetic analysis (Blanco et al 2020). Finally, a recent study using threegene PCR and high resolution melting analysis showed encouraging accuracy for East African wildlife species identification (Ouso et al 2020).…”
Section: Poachingmentioning
confidence: 99%
See 1 more Smart Citation
“…While its long-read length (of up to ∼1 Mb, [6]) makes it very attractive for the generation of de novo genome assemblies (see e.g. [6,7]), its low upfront costs (∼1000 USD) and its portability offer huge advantages for DNA-or metabarcoding experiments in countries with limited infrastructure and funds for molecular biomonitoring [8][9][10][11][12], and for teaching and local capacity building [13,14]. The use of the MinION has been extensively investigated for biodiversity research and biomonitoring projects (reviewed in [15]).…”
Section: Applications To Species Identificationmentioning
confidence: 99%